Hypoxia Exacerbates Inflammatory Acute Lung Injury via the Toll-Like Receptor 4 Signaling Pathway - Wu, Gang; Xu, Gang; Chen, De-Wei; Gao, Wen-Xiang; Xiong, Jian-Qiong; Shen, Hai-Ying; Gao, Yu-Qi (Frontiers in Immunology, 2018)
Acute lung injury (ALI) is characterized by non-cardiogenic diffuse alveolar damage and often leads to a lethal consequence, particularly when hypoxia coexists. The treatment of ALI remains a challenge: pulmonary inflammation and hypoxia both contribute to its onset and progression and no effective prevention approach is available. Here we aimed to investigate the underlying mechanism of hypoxia interaction with inflammation in ALI and to evaluate hypoxia-inducible factor 1α (HIF-1α) - the crucial modulator in hypoxia - as a potential therapeutic target against ALI. First, we developed a novel ALI rat model induced by a combined low-dose of lipopolysaccharides (LPS) with acute hypoxia. Secondly, we used gene microarray analysis to evaluate the inflammatory profiles of bronchi alveolar lavage fluid (BALF) cells of ALI rats. Thirdly, we employed an alveolar macrophage cell line, NR8383 as an in vitro system together with a toll-like receptor 4 (TLR4) antagonist TAK-242, to verify our in vivo findings from ALI animals. Lastly, we tested the therapeutic effects of HIF-1α augmentation against inflammation and hypoxia in ALI. We demonstrated that: (i) LPS upregulated inflammatory genes, TNF-α, IL-1β, and IL-6, in the alveolar macrophages of ALI rats, which were further enhanced when ALI combined with hypoxia; (ii) Hypoxia-exposure could further enhance the upregulation of alveolar macrophageal TLR4 that was noticed in LPS-induced inflammatory ALI, conversely, TLR4 antagonist TAK-242 could suppress the macrophageal expression of TLR4 and inflammatory cytokines, including TNF-α, IL-1β, and IL-6, suggesting that the TLR4 signaling pathway as central link between inflammation and hypoxia in ALI; (iii) Manipulation of HIF-1α in vitro could suppress TLR4 expression induced by combined LPS and hypoxia, via suppressing promoter activity of the TLR4 gene; (iv) Preconditioning augmentation of HIF-1α in vivo by HIF hydroxylase inhibitor, DMOG excreted protection against inflammatory and hypoxic processes in ALI. Together, we see that hypoxia can exacerbate inflammation in ALI via the activation of the TLR4 signaling pathway in alveolar macrophages and predispose impairment of the alveolar-capillary barrier in the development of ALI. Targeting HIF-1α can suppress TLR4 expression and macrophageal inflammation, suggesting the potential therapeutic and preventative value of HIF-1α/TLR4 crosstalk pathway in ALI.